LEGITIMASI PENGGUNAAN KEKUATAN BERSENJATA PADA KONFLIK PEREBUTAN WILAYAH ANTARA INDIA DAN PAKSITAN (KAJIAN BERDASARKAN TEORI JUST WAR) - Syauqi Libriawan (Faculty of Law Universitas Sebelas Maret, 2024)
The conflict between India and Pakistan starts with the territorial conflict of a region called Kashmir. The tension of the conflict arises along with the use of force, makes the territorial conflict become an armed conflict. This study explains the conflict between India and Pakistan over Kashmir territory on 1947 and 1965. The objectives of this study are to determine whether the use of force on territorial conflict can be legitimate and to determine the applications of international humanitarian law on the territorial conflict. This study uses case approach and conseptual approach. This study also uses deductive methods, by using the analysis of the legitimate use of force by a state based on just war theory in common as major premise, and the use of force by India and Paksitan on territorial conflict as minor premise.